2009
DOI: 10.1172/jci37338
|View full text |Cite
|
Sign up to set email alerts
|

The neuropathic potential of anti-GM1 autoantibodies is regulated by the local glycolipid environment in mice

Abstract: Anti-GM1 ganglioside autoantibodies are used as diagnostic markers for motor axonal peripheral neuropathies and are believed to be the primary mediators of such diseases. However, their ability to bind and exert pathogenic effects at neuronal membranes is highly inconsistent. Using human and mouse monoclonal anti-GM1 antibodies to probe the GM1-rich motor nerve terminal membrane in mice, we here show that the antigenic oligosaccharide of GM1 in the live plasma membrane is cryptic, hidden on surface domains tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 60 publications
7
81
0
Order By: Relevance
“…At hemidiaphragm NMJs sensitized by anti-GM1 Ab, but prior to exposure with NHS, MEPP frequency was normal, at approximately 1.5/s, as expected ( Figure 5, A and B) (22). When these preparations were immediately exposed to NHS, a large elevation in the MEPP frequency - to a level of 56.6 ± 9.6/s (n = 51 NMJs from 2 muscles) - occurred, as expected from earlier studies with this Ab (23). When anti-GM1 Ab-sensitized preparations were incubated for 1 hour at 37°C prior to exposure to NHS, the increase in MEPP frequency was significantly attenuated, by approximately 75% (13.1 ± 3.5/s; n = 46 NMJs; P < 0.001).…”
Section: Figuresupporting
confidence: 84%
See 1 more Smart Citation
“…At hemidiaphragm NMJs sensitized by anti-GM1 Ab, but prior to exposure with NHS, MEPP frequency was normal, at approximately 1.5/s, as expected ( Figure 5, A and B) (22). When these preparations were immediately exposed to NHS, a large elevation in the MEPP frequency - to a level of 56.6 ± 9.6/s (n = 51 NMJs from 2 muscles) - occurred, as expected from earlier studies with this Ab (23). When anti-GM1 Ab-sensitized preparations were incubated for 1 hour at 37°C prior to exposure to NHS, the increase in MEPP frequency was significantly attenuated, by approximately 75% (13.1 ± 3.5/s; n = 46 NMJs; P < 0.001).…”
Section: Figuresupporting
confidence: 84%
“…Two signals were considered as strongly colocalizing if the Manders coefficient was equal to or greater than 0.7 (56,57). For quantitative assessment of Ab and complement levels in all ex vivo TS preparations, images were collected using confocal microscopy (Zeiss LMS 5 Pascal) under constant acquisition settings and quantified using ImageJ software (http://rsbweb.nih.gov/ij/) as previously described (23). For illustrations, all images were collected using a Zeiss AxioImager equipped with an Apotome and AxioVision software.…”
Section: Methodsmentioning
confidence: 99%
“…If we suppose indeed that variable proportions and contiguities of individual gangliosides may be expressed in different neural membrane, it is tempting to speculate that this may lead to the formation of new antigens but also to the different expressions or hiding of reactive epitopes in different neural membranes. A brilliant support to this hypothesis was recently given by Greeshields et al (2009) who showed that the GM1 binding epitope may be often hidden in mice membranes by contiguous gangliosides and particularly by GD1a, so that the pathogenic effect of anti-GM1 antibodies may vary depending on recognition of exposed or cryptic antigens. This may theoretically help in explaining the different pathogenic effects of apparently similarly reacting antiganglioside antibodies.…”
Section: Discussionmentioning
confidence: 96%
“…Numerous investigators over several decades and several continents have attempted to determine whether these antibodies are pathogenetic and how they mediate damage. In summary, many collaborative efforts have demonstrated that anti-GM1 and anti-GQ1b antibodies bind to peripheral nerve and neuromuscular junctions 64,65 , and anti-GD1a antibodies bind to the nodes of Ranvier, paranodal myelin and neuromuscular junction 66,67,68 . Upon binding, the antibodies activate the complement cascade, resulting in formation of the membrane attack complex, disruption of sodium channel clusters at the node of Ranvier with disruption of nodal architecture 69 , and calcium influx and calpain-dependent neuronal and glial injury at the neuromuscular junction 70,71 .This injury can be ameliorated with complement inhibitors 72,73 .…”
mentioning
confidence: 99%